1999
DOI: 10.1097/00000421-199910000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel and G-CSF in Previously Untreated Patients With Extensive Stage Small-Cell Lung Cancer

Abstract: Paclitaxel is an antimicrotubule agent that interferes with cell division. It has demonstrated promising single-agent activity against non-small-cell lung cancer. The purpose of this study was to evaluate the therapeutic effectiveness of paclitaxel in previously untreated patients with extensive stage small-cell lung cancer (SCLC). The study was designed as a two-stage phase II trial. All patients who entered received paclitaxel by intravenous infusion at a dose of 250 mg/m2 during 24 hours. Granulocyte colony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…The study actually enrolled 38 patients in three years and it was decided to halt the trial because of the highly positive experience with this concurrent chemo-radiotherapy. This decision was also weighed by data from other studies (Kirschling et al, 1999;Thomas et al, 2001). Survival was analysed using a Kaplan Meier curve.…”
Section: Discussionmentioning
confidence: 99%
“…The study actually enrolled 38 patients in three years and it was decided to halt the trial because of the highly positive experience with this concurrent chemo-radiotherapy. This decision was also weighed by data from other studies (Kirschling et al, 1999;Thomas et al, 2001). Survival was analysed using a Kaplan Meier curve.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has shown considerable anti-tumour activity in chemotherapy naive patients with SCLC (Kirschling et al, 1994;Ettinger et al, 1995). Therefore, we initiated a phase II trial of paclitaxel (taxol) in patients with clinically resistant SCLC, which is the subject of this report.…”
mentioning
confidence: 99%
“…This drug showed encouraging single-agent activity as second-line treatment: in patients with ED pretreated with CDE as first-line combination, single-agent paclitaxel showed an overall response rate of 29%, which is at the upper level of activity for any single agent in this setting (Smit et al, 1998). An interesting activity was also observed in untreated patients; in the Eastern Cooperative Oncology Group (ECOG) phase II study a 34% remission rate and a 43-week median survival were observed (Ettinger et al, 1995); the North Central Cancer Treatment Group (NCCTG) also reported a 53% response rate in 43 untreated patients (Kirschling et al, 1999). These phase II studies, evaluating the activity of paclitaxel in ED -SCLC, provided the basis for inclusion of this drug in polichemotherapy regimens.…”
mentioning
confidence: 95%